(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
This recently published essay by Lisa Unangst (SUNY Empire State University) builds upon a growing attention to the intersection of displacement and alternative higher education pathways. It analyzes how the current literature in the field addresses Prior Learning Assessment serving displaced learners. Citation Unangst, L. (2025). Social inequality contested: Prior learning assessment in the context of displacement. In A. Curaj, C. M. Hâj, & R. Pricopie (Eds.), European higher education area 2030: Bridging realities for tomorrow’s higher education. FOHE-BPRC 2024. Springer. https://doi.org/10.1007/978-3-031-75140-0_16